Transient flow of liquid in plastic pipes - Urbanowicz, Kamil (Strojniški vestnik, 2020)
Nowadays, plastic pipes play a key role in fluid conveyance, for example, in urban water supply systems. Dynamic analysis of designed water pipe networks requires the use of numerical methods that allow for solving basic equations that describe transient flows occurring in plastic pipes. In this paper, the main equations were formulated with pressure (p) and velocity (v) as the principal variables. A novel simplified retarded strain solution is used to properly model the pipe-wall viscoelasticity effect during transient flow process. Unsteady friction is calculated with the use of a filtered weighting function (with three exponential terms). The proposed numerical method enables the efficient modelling of transient flow in plastic pressurized pipes. Extensive simulations are performed and compared with experimental results known from three different European research centres (London, Cassino, and Lyon), with the aim of demonstrating the impacts of plastic pipe properties and frequency-dependent hydraulic resistance on transient pipe flow oscillations. The effectiveness of the proposed method for determining the creep functions of plastic pipes is also examined and discussed.
Keywords: method of characteristics; nestabilno trenje; numerične metode; plastic pipes; plastične cevi; transient flow; unsteady friction; viscoelasticity; viskoelastičnost; water hammer